Ultrathin fluidic laminates for large-area Façade integration and smart windows - Heiz, Benjamin P. V.; Pan, Zhiwen; Lautenschlager, Gerhard; Sirtl, Christin; Kraus, Matthias; Wondraczek, Lothar (Advanced Science, 2017)
Buildings represent more than 40% of Europe’s energy demands and about one third of its CO2 emissions. Energy efficient buildings and, in particular, building skins have therefore been among the key priorities of international research agendas. Here, glass-glass fluidic devices are presented for large-area integration with adaptive façades and smart windows. These devices enable harnessing and dedicated control of various liquids for added functionality in the building envelope. Combining a microstructured glass pane, a thin cover sheet with tailored mechanical performance, and a liquid for heat storage and transport, a flat-panel laminate is generated with thickness adapted to a single glass sheet in conventional windows. Such multimaterial devices can be integrated with state-of-the-art window glazings or façades to harvest and distribute thermal as well as solar energy by wrapping buildings into a fluidic layer. High visual transparency is achieved through adjusting the optical properties of the employed liquid. Also secondary functionality, such as chromatic windows, polychromatism, or adaptive energy uptake can be generated on part of the liquid.
CRIS-Team Scopus Importer:2023-04-20